The Influence of Social Media Content and Digital Marketing Implementation on the Image of Jglow Skincare - Sandi Nugraha; Maya Retnasary (Kanal: Jurnal Ilmu Komunikasi, 2023)
Social media is a means for many groups, both from individuals to institutions to communicate with each other. The form of messages communicated is usually known as content. Brands usually use social media as a tool to communicate their messages to the public. Digital marketing is brand marketing activities digitally, but digital marketing is also often used by brands for branding media to the public. The purpose of this research is to determine the effect of social media content and digital marketing on Jglow's brand image partially or simultaneously. This research uses quantitative research methods in the form of a survey. A sample of 250 people who used skincare in the city of Bandung were asked to fill out a questionnaire that served as a data collection tool. using the Likert scale measurement and the Slovin formula. The results of this study are, social media content partially has a significant influence on Jglow's image, with a percentage of 50.9%. Likewise digital marketing with an influence percentage of 54.1%. Simultaneously Social media content and digital marketing have a significant influence on image with a percentage of 67.4%. From these percentages it can be stated that the two variables have a significant and positive impact on the Jglow brand image in the city of Bandung.